Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1744-1617.2007.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Youth Placed in Unlicensed, Unregulated Residential “Treatment” Facilities

Abstract: Throughout the country, there is considerable inconsistency in how states regulate residential treatment programs for youth. In states with little oversight, the health and safety of youth are unprotected and they may be subject to substandard treatment, rights violations, and/or abuse. Three initiatives to address this issue are reported: (1) an Internet survey of youth who are former residents, (2) a four‐state pilot study of how states regulate and monitor residential programs, and (3) a bridge‐building con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Lower socio-economic parents and adolescents may be completely excluded from this form of therapy. In a study conducted by Behar et al (2007) in which wilderness camp participants were surveyed, they reported that half of the families had an income of $100,000 or more. Currently, most insurance companies will not pay for wilderness therapy or only pay a small portion.…”
Section: Program Costmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower socio-economic parents and adolescents may be completely excluded from this form of therapy. In a study conducted by Behar et al (2007) in which wilderness camp participants were surveyed, they reported that half of the families had an income of $100,000 or more. Currently, most insurance companies will not pay for wilderness therapy or only pay a small portion.…”
Section: Program Costmentioning
confidence: 99%
“…Research is beginning to surface on the effectiveness of established Wilderness Therapy programs (Russell 2005). However, wilderness camps have been under the microscope in the past few years for accusations of the treatment of the residents in the camps (Behar et al 2007). More specifically are the accusations of abuse and neglect leading to deaths of more than 10 adolescents since 1990 and scores of reports of abuse and neglect.…”
mentioning
confidence: 98%
“…(p. 1250; italics added) Although this description is an inaccurate representation of many wilderness programs and the current OBHIC guidelines, such programs do exist. As a result, wilderness therapy programs-particularly those which are unlicensed or unregulated-have recently come under intense scrutiny in media (Krakauer 1995;''When 'tough love''' 2007), academic (Behar et al 2007;Friedman et al 2006;Meyer 2007), and political (Government Accountability Office [GAO] 2007[GAO] , 2008''Stop Child Abuse'' 2008) forums. Importantly, Koocher's (2003) sentiment that wilderness programs are void of therapeutic content highlights several of the challenges that currently face the field, and the onus is on the wilderness therapy programs and practitioners to provide high-quality professional and ethical treatment that counters this view.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Some of these issues have also been detailed in several articles by a group of researchers called ASTART (Alliance for the Safe, Therapeutic, and Appropriate Use of Residential Treatment), with a particular focus on mistreatment and abuse of youth in residential care. Examples of these articles include Behar, Friedman, Pinto, Katz-Leavy, & Jones, (2007) ;Friedman, Pinto, Behar, Bush, Chirolla, & Epstein, et al (2006);and Pinto, Friedman, & Epstein (2005) and make a strong case for regulations to stop abuses occurring primarily at unlicensed and unregulated facilities. They advocate adoption of policies recommended by the American Bar Association (2007) that included closing facilities who cannot provide evidence of their efficacy.…”
Section: Best Practice In Adolescent Residential Mental Health Treatmentmentioning
confidence: 99%
“…Cited as fact in several places (Behar, Friedman, Pinto, Katz-Leavy, & Jones, 2007;Pinto, Friedman, & Epstein, 2005) are figures from a newspaper article that estimates (without citing any evidence) 10,000 to 14,000 school age children in private residential treatment (Rubin, 2004). Friedman (2009), coordinator of A START said in a presentation during "Abuse of Youth in Residential Treatment: A Call to Action," "We were dismayed when they (GAO) were no more successful than others in coming up with estimates of the number of youth in private residential placements" (p. 3).…”
Section: How Many Programs and How Many Served?mentioning
confidence: 99%